2018
DOI: 10.3892/or.2018.6284
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms and protein expression of P53 and BRCA1 in preneoplastic and neoplastic rat mammary glands

Abstract: Breast cancer is the most common type of cancer and the leading cause of cancer-related deaths among women in the United Arab Emirates and worldwide. Although many factors contribute to the high incidence of breast cancer, a considerable number of cases are related to environmental factors. In the present study, breast cancer was induced in female rats using a single dose, 80 mg/kg body wt, of the environmental carcinogen 7,12-dimethylbenz[a]anthracene (DMBA). The aim of the present study, was to characterize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Dastjerdi MN 30 reported that TP53 codon 72 polymorphism may be correlated with p53 overexpression and increased risk for colorectal cancer. Al-Dhaheri et al 31 reported that p53 overexpression in the progression towards malignancy of preneoplastic and neoplastic rat mammary glands associated with TP53 polymorphism; while Rybárová et al 32 reported that no statistically signi cant difference was found between TP53 codon 72 polymorphism and p53 protein expression in human breast cancer. These variations in results might be possible due to organ speci city and species differences.…”
Section: Discussionmentioning
confidence: 99%
“…Dastjerdi MN 30 reported that TP53 codon 72 polymorphism may be correlated with p53 overexpression and increased risk for colorectal cancer. Al-Dhaheri et al 31 reported that p53 overexpression in the progression towards malignancy of preneoplastic and neoplastic rat mammary glands associated with TP53 polymorphism; while Rybárová et al 32 reported that no statistically signi cant difference was found between TP53 codon 72 polymorphism and p53 protein expression in human breast cancer. These variations in results might be possible due to organ speci city and species differences.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, P53 expression is a DNA damage biomarker. [35][36][37][38] DMBA exposure in mice stimulated the expression of both p53 and p21WAF1 indicating a DNA injury and in p53-deficient mice, DMBAinduced skin papillomas exerted malignant conversion. 36 In DMBA-induced hamster buccal-pouch carcinogenesis, p53 and iNOS genes were activated in the buccal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…36 In DMBA-induced hamster buccal-pouch carcinogenesis, p53 and iNOS genes were activated in the buccal mucosa. 37 The important role of p53 against genomic damage, enhanced genotoxicity of MNU in p53-semideficient state and upregulation of p53 with the progression towards malignancy have been shown in DMBA-induced breast cancer in rats. 38,39 In another study preventive role of green tea extracts has been shown in BaP-induced lung carcinoma in rats, in association with stimulation of p53 levels.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer is the most common cancer and the leading cause of cancer death in women worldwide, many factors contribute to initiation and progression of breast cancer [1,2]. As angiogenesis is essential for tumor growth and metastasis, inhibiting tumor-associated angiogenesis has long been a promising target in limiting cancer progression [3,4].…”
Section: Introductionmentioning
confidence: 99%